Analisis Pengaruh Dagree Of Operating Leverage (DOL) Terhadap Return On Asset (ROA) Pada PT. Indonesia Prima, Tbk - Jumratu Jumratu; Nurhayati Nurhayati; Aris Munandar (Jurnal Manajemen Informatika & Teknologi, 2025)
Degree of Operating Leverage is one of the efforts to measure how much influence changes in revenue have on a company's operating profit. The purpose of this study is to determine the effect of Degree of Operating Leverage on Return on Assets at PT. Indonesia Prima Tbk. The type of data used is quantitative data using associative research. The research instrument is a list of tables with a sample of 10 years of financial reports. Data collection techniques use documentation and literature studies. Data analysis uses simple linear regression, correlation coefficients, determination tests and t-tests. The results of the study indicate that Degree of Operational Leverage (DOL) has no significant effect on Return on Assets (ROA) at PT. Indonesia Prima Tbk.